Hedonic pricing model for impact of infrastructure facilities on land rates: case study of Kudi Bhagtasni, Jodhpur, India. (2nd October 2021) - Vaishampayan, Shruti; Dev, Meghraj; Patel, Upendra
Residential land prices vary significantly from area to area because of their geographical, locational, environmental and socio-economic characteristics. Residential land values are determined by multiple factors like access road width, distance to main road, distance to central business district, proximity to green space, hospital, school, etc. In this study, a detailed data set of various infrastructure facilities such as roads, water supply, sewerage are collected to analyse their impact on land prices and establish a Hedonic Pricing Model for impact on prices of residential properties in nine different sectors of Kudi Bhagtasni area in Jodhpur, Rajasthan India. A total of 131 samples were collected to establish this model for the monitoring period 2019-2020 for determining the market value of land rates of properties in the selected case study.